Injection of Chemotherapeutic Microspheres and Glioma III: Parameters to Optimize Efficacy - Dwaine F. Emerich; Shelley R. Winn; Raymond T. Bartus Ph.D. (Cell Transplantation, 2002)
Injectable microspheres may provide a means of providing local, sustained exposure of glioma to chemotherapeutics to improve patient survival. Using a rodent model of surgically resected glioma, we previously demonstrated that direct injections of chemotherapeutic microspheres into the tissue surrounding a resection cavity provide superior survival effects over injections of the same microspheres directly into the surgical cavity. The present experiments extended this novel observation by exploring several parameters related to the use of intraparenchymal injections of chemotherapeutic microspheres to treat glioma. Using a rat model of resected glioma, several principles regarding the use of local sustained release carboplatin microspheres were established. First, an inverted U dose–response was observed, wherein further dose escalation beyond the optimal dose was not efficacious and indeed produced significant local toxicity. Second, it was necessary to expose approximately 40% of the tumor margin to sustained release carboplatin in order to increase survival in this model. Survival was not enhanced when the proportion of the tumor margin exposed to carboplatin was only 20%. Third, the distribution of the chemotherapeutic microsphere injections along the tumor perimeter was shown to be important, requiring that the entire perimeter be proportionately exposed to the chemotherapeutic agent. Together, these data continue to support the development of chemotherapeutic microspheres for treating glioma. However, they also caution that a number of fundamental parameters can profoundly influence the efficacy that might be expected from local sustained delivery. Careful attention to these principles is not only required if chemotherapeutic microspheres are to be used efficaciously, but these principles should provide a foundation to further optimize the potential of this and other polymeric delivery systems under development for local, intraparenchymal drug delivery to glioma.